Fostering institutional creativity at multiple levels: Towards facilitated institutional Bricolage - Merrey, D.; Cook, Simon (2012)
Problems occur when institutional arrangements for collective management of food and water systems fail to meet demands. Many of the problems characterising river basins and other collectively managed water resource systems can be ascribed largely to the failure of institutions to enable problems beyond the individual to be managed collectively. The nature of these demands, and the institutional responses to them, vary widely and are not amenable to simple definitions and prescriptions. We begin with a brief review of conventional approaches to analysing institutions and organisations, focused largely, but not exclusively, on river basins. We observe that attempts to reduce the institutional landscape of river basins to over-simplistic formulas introduces more problems than solutions, because the reality is that institutions evolve through complex creative processes that adopt and adapt diverse ingredients - rather like making a stew. Despite such intricacies, institutions are clearly non-random, so we continue a search for a means of describing them. We adopt the concept of bricolage, as proposed by Cleaver and others, and use it to show the value of promoting and facilitating an organic creative approach to building and strengthening river basin and other water management institutions.